The Third Worker: Assessing the Trade-off between Employees and Contractors - Pedro S. Martins (Institute for the Study of Labor (IZA), 2016)
Firms make labour demand decisions not only between permanent and non-permanent employees but also increasingly more between employees and contractors. Indeed, this third work format can be attractive, also when employment protection law is restrictive. This paper examines empirically this scarcely researched trade-off drawing on a recent reform in Portugal that cut the severance pay of new employee hires while leaving unchanged the regulations affecting contractors. Our analysis draws on difference-in-differences methods and original high-frequency firm-level panel data on both employees and contractors. We find that the reduction in severance pay had a large relative positive effect on the wage bills and worker counts of employees compared to contractors. This result, robust to a number of checks, highlights the role of labour regulations as an additional driver of more flexible labour formats.
Keywords: J23; J41; J63; 330; employment law; segmentation; duality; future of work